THE INFLUENCE OF PERCEIVED BEHAVIOUR CONTROL, SUBJECT NORMS AND ATTITUDE ON THE PURCHASE INTENTION OF THE CUSTOMERS - Yajid, Mohd Shukri Ab; shukri, Sakinah mohd; Azam, S.M. Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
The aim related to the current literature is to examine the role of perceived behaviour control, subject norms and attitude on the purchase intension of the customers in Malaysia. Data were gathered from the customer relation manager of the companies and SPSS employed to test the hypotheses. The results show that positive nexus among the perceived behaviour control and purchase intension, subject norms and purchase intension and attitude and purchase intension.